Extremely rare case of intravascular solitary fibrous tumour in the inferior vena cava with review of the literature - Jingyuan Fan; Jinfeng Qiu; Qingjun Wei (BMC, 2019)
Abstract Background Solitary fibrous tumour (SFT) is a mesenchymal tumour of fibroblastic type, and it develops in almost any part of the human body. However, according to previous studies, the occurrence of intravascular SFTs is extremely rare. Case presentation We reported a case of intravascular SFT in a 67-year-old woman who has been experiencing swelling and pain in the right leg for 2 months. Computed tomography venography scan revealed a well-defined mass obstructing the inferior vena cava (IVC). Surgical resection was performed, and histopathologic and immunohistochemical results were consistent with SFT. Further, next-generation sequencing (NGS) analysis was performed, and results revealed two tumour-related gene mutations (deletion of PMS2 and variation of ESR1 [L536P]). The patient did not receive any adjuvant therapy, and no signs of tumour progression were observed during the 6-month follow-up. Conclusion To the best of our knowledge, this study first presented about SFT arising from the IVC and carried out an NGS analysis to validate the molecular mechanism of such condition.